Single-institution analysis of the prevalence, indications and outcomes of end-of-life radiotherapy. (September 2021) - Christ, Sebastian M.; Schettle, Markus; Seiler, Annina; Guckenberger, Matthias; Blum, David; Andratschke, Nicolaus; Hertler, Caroline
Highlights: Survival prognostication and patient selection remain challenging tasks. End-of-life radiotherapy until one week before death showed a patient benefit. Treatment prescribed within one week of death often had to be discontinued. Therapy needs to take into account patient preferences for the last phase of life. Abstract: Background: Radiotherapy plays an important role for symptom control in advanced stage cancer patients. Yet patients need to be carefully selected, and its use and benefits must be weighed against time spent under treatment and patient priorities in the last phase of life. In this study, we assess prevalence, indications and outcomes of radiotherapy close to death. Methods: We screened all radiotherapy treatments performed at the Department of Radiation Oncology of the University Hospital Zurich between January 2010 and December 2019 to identify those which occurred near patients' end-of-life. Analyzed data was extracted from the database of the Comprehensive Cancer Center Zurich, the treatment planning system Aria® and the electronical medical records system KISIM®. Results: Within 60 days of death, 377 radiotherapy courses were prescribed to 280 patients, which constitutes 3.4% of all radiotherapy courses administered over the last decade at our department. Within 60–31, 30–8, and 7–0 days to death 164, 159, and 54 radiotherapy courses were prescribed, respectively. The most frequent treatment sites were brain (N = 122, 32%) and bone (N = 119, 32%), and there was no statistically significant difference in treatment site between the three sub-groups. The most common regimen was 10x3Gy (N = 130, 35%) in all three sub-groups (p = 0.23). Radiotherapy finished more than one week before death was associated with high completion rates (>80%) and treatment benefit (>55%). Conclusion: Patient selection and survival prognostication remains challenging for radiation oncologists. While radiotherapy achieved high completion and success rates until one week before death, treatment within one week of death should be restricted to carefully selected patients or avoided altogether.